An Analysis of Word Formation Process in I Am Malala Novel by Malala Yousafzai - Sinulingga, Desi Rahma Yuni Br.; Deliana, Deliana (RADIANT: Journal of Applied, Social, and Education Studies, 2022)
The aim of this research is to find the used of the types and the most dominant types of word formation process in I Am Malala novel by Malala Yousafzai. This is a qualitative descriptive research by Miles and Huberman (2014). The words were analized by using Oâ€™Grady and Guzman (2010) theory. From the analysis, the writer found 12 from 14 word formation types process with the classifying. 33 of Borrowing (3,09%), 130 of Compounding (12,17%), 4 of Reduplication (0,37%), 318 of Inflection (29,78%), 34 of Suppletion (3,18%), 75 of Internal Change (7,02%), 5 of Coinage (0,47%), 5 ofÂ  Onomatopoeia (0,47%), 53 of Acronyms (4,97%), 5 of Clipping (0,47%) ,14 of Back Formation (1,31%), and 392 of Derivation (36,70%). Also found the most dominant type is Derivation. It has 36,70% of the total term. The total of Derivation is 392 words from total 1.068 words.